Harm Avoidance and Self-Directedness Characterize Fibromyalgic Patients and the Symptom Severity - Leombruni, Paolo; Zizzi, Francesca; Miniotti, Marco; Colonna, Fabrizio; Castelli, Lorys; Fusaro, Enrico; Torta, Riccardo (Frontiers in Psychology, 2016)
Abstract Objective: Evidence in the literature suggests peculiar personality traits for fibromyalgic patients, and it has been suggested that personality characteristics may be involved in patients' different symptomatic events and responses to treatment. The aim of the study is to investigate the personality characteristics of Italian FM patients and to explore the possibility of clustering them considering both personality traits and clinical characteristics. Design: The study used a cross-sectional methodology and involved a control group. A self-assessment procedure was used for data gathering. The study included 87 female FM patients and 83 healthy females. Patients were approached and interviewed in person during a psychiatric consultation. Healthy people were recruited from general practices with previous telephone contact. Main Outcome Measures: Participants responded to the Hospital Anxiety and Depression Scale (HADS), the Temperament and Character Inventory (TCI), the Fibromyalgia Impact Questionnaire (FIQ) and the Short-Form-36 Health Survey (SF-36). Results: FM patients scored significantly different from healthy participants on the Harm-Avoidance (HA), Novelty Seeking (NS) and Self-Directedness (SD). Two clusters were identified: patients in Cluster 1 (n=37) had higher scores on HA and lower scores on RD, SD and Cooperativeness and reported more serious fibromyalgia and more severe anxious-depressive symptomatology than did patients in Cluster 2 (n=46). Conclusion: This study confirms the presence of certain personality traits in the FM population. In particular, high levels of Harm Avoidance and low levels of Self-Directedness characterize a subgroup of FM patients with more severe anxious-depressive symptomatology. According to these findings, personality assessment could be useful in the diagnostic process to tailor therapeutic interventions to the personality characteristics.